Digital transactions in floating markets: methods for exploring the intentions of floating market merchants using QRIS - Nurhayati Nurhayati; Nurhaeni Nurhaeni (Institute of Computer Science (IOCS), 2023)
variety of online-based economic activities to meet various community needs. Along with the development of digital platforms that facilitate the process of trade transactions, the development of digital-based payment technology has also occurred with the emergence of the Quick Response Code Indonesian Standard (QRIS). Currently, QRIS has begun to be used by Lok Baintan floating market merchants as a more efficient non-cash payment system. The advantages possessed by QRIS include being able to accept switching from various types of different merchants quickly and safely. This study aims to examine the factors that shape the intention of floating market merchants to use QRIS. This research method uses qualitative methods, by conducting interviews with several merchants at the Lok Baintan floating market. Data analysis using NVivo software. The results of the study show that currently, the spread of the use of QRIS by merchants in floating markets is still very minimal. This is caused by a lack of readiness and understanding of the benefits of QRIS for merchants. Another reason why floating market merchants are not actively using QRIS is that the funds from the sale go directly to the bank account, so when merchants want to use the money for their daily needs, they have to withdraw the funds first